Implementasi Assesment Akademik Dan Perkembangan Anak Berkebutuhan Khusus - Meli Mustika Sari; Pradita Rizki Putri; Opi andriani (LPPM Politeknik Pratama, 2024)
Inclusive education is a process of responding to the needs of all diverse students. Various efforts can be made through changes and modifications in content, approaches, structures and strategies that can accommodate the needs of all students according to their age group. Inclusive education begins with education for all that does not discriminate against anyone, including children with special needs. Children with special needs are children who experience limitations and obstacles in aspects of development, both cognitive, physical, social and emotional, so they require special services that must be met. Their needs are based on the limitations or obstacles they experience. The types of services provided to them cover all aspects of children's lives, both academic and non-academic services. There are several groups of children with special needs, including: children with visual impairments (blind), children with hearing impairments (deaf impaired), children with intellectual impairments (mental retardation), children with physical and motor impairments (impaired), children with pervasive behavioral disorders (Autism). , AD-HD Apart from that, the identification process also tries to classify children into certain groups based on the type of obstacles the child has. The next process after the child is identified is assessment. Assessment is a systematic and comprehensive assessment in gathering further information about the child regarding deficiencies, the child's potential and needs. The results of the assessment that have been carried out become the basis or reference for designing and implementing the provision of services to children with special needs. So that the data that is traced during identification or assessment is real and real data from the child. Identification and assessment are carried out by inclusive schools as a step to carry out mapping for students who have disabilities or special needs. Mapping is carried out to determine the types of needs each child has so that the appropriate educational services for children at school can be identified.